Adaptive robust tracking control for an offshore ship-mounted crane subject to unmatched sea wave disturbances - Qian, Yuzhe; Fang, Yongchun; Lu, Biao (Mechanical systems and signal processing, 2019)
•The paper firstly achieves adaptive robust tracking control for offshore ship-mounted cranes.•Unmatched sea wave disturbances are taken into consideration.•Comparative hardware experiments verify the effectiveness of the proposed method. An offshore ship-mounted crane consisting of a trolley, a wire, and a payload, is a typical nonlinear underactuated system, which suffers from unmatched disturbances mainly caused by sea waves and currents. Besides, unknown or uncertain parameters may cause vertical positioning errors or make accurate gravity compensation impossible, which may induce various risks during the transportation process. In terms of the aforementioned problems, this paper studies the adaptive robust tracking control problem for an offshore ship-mounted crane. In particular, a new adaptive robust coupling control approach, with adaptive laws included to deal with unknown parameters, and robust terms included to handle unknown disturbances, especially unmatched disturbances, is constructed in this paper, which achieves simultaneous load swing suppression and disturbances elimination. Without any approximation to the original nonlinear model, it is rigorously proven that the proposed method can ensure the stability of the overall crane system’s equilibrium point, as supported by Lyapunov techniques. Finally, some contrast simulations and experimental results are collected to verify the superior performance of the proposed controller.